Perencanaan Dan Pembuatan Alat Uji Pemipaan untuk Menganalisis Kehilangan Tekanan dengan Menggunakan Software Pipe Flow Expert - Dinni Agustina; Ratna Sary; Martunis Martunis (Jurnal Teknik Mesin Unsyiah, 2018)
The most dominant water distribution system used is the preparation system, in which each system has its respective advantages and disadvantages, where the weakness of the piping system is the unavoidable pressure loss caused by the connection factor and the surface roughness of the material used. Head losses are a flow loss phenomenon within the piping system. Head losses overall on 12.1 m piping system, This value can be from the sum of head losses on the pipe diameter of 25.4 mm with a length of 3400 mm of 0.0786 m. Head losses on pipe diameter 19 mm with length 3800 mm at 1.52 m and head losses at pipe diameter 12,7 mm with length 2800 mm equal to 10,59 m. The pressure in main pipe is 1,12 atm and pressure at output valve Water 1 atm based on the calculation method, the flow velocity in the main pipe 1 m/s, the speed in the second pipe 1.76 m/s, the speed in the last pipe of 3.34 m/s. Pipe used is PVC with diameter 1 inch, ¾ inch, and ½ inch. While the model pipe flow expert program 5.12 pressure on the main pipe of 1.18 atm, the pressure at the end of the valve 1 atm, the speed in the main pipe 1.077 m/s, the speed in the second pipe of 1.79 m/s, and the speed In the last pipe 3.3 m/s. The difference in velocity between modeling and calculation is due to the difference in internal diameter of the model by calculation, where the difference in value is 0.2 mm. The water debit generated from the test equipment is 1.3 m3/h, while using the software of 1.8 m3/h. The difference between the results of the experiment and modeling if the percentage of 270/0 is suppressed.